The correlation of personal characteristics and professional value orientations of representatives of the socionomical sphere of employment - Natalya А. Samoylik (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The results of the empirical study of the correlation of features and professional value orientations of representatives of the "person-to-person" sphere of labor are presented in the article.On the basis of correlation analysis it is found that specialists with behavioral type of professional value orientations express extroversion, sensitivity and emotivity. Representatives of this group are motivated to achieve professional goals, develop professional competencies and pay special attention to the problems of other people. Respondents with emotional type of professional value orientations have anxiety, which manifests itself in a specific form of activity aimed at establishing and maintaining productive relationships. Employees of the social field with a cognitive type of profes- sional value orientations have spontaneity, which is expressed in the absence of a clear algorithm of job responsibilities, due to the lack of strict requirements for the implementation of the process of interpersonal interaction. Professionally necessary personal characteristics for the representatives of this group are goal-setting, interpersonal relationships and qualities that significantly affect the efficiency of work.In conclusion, the author assumes that respondents have such common personal characteristics as orientation to the world of another person, sociability, sensitivity to the problems of the interlocutor, interest in the effective organization of the process of interpersonal interaction.